PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH (ICM)TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VII SMP NEGERI 1 LINGGO SARI BAGANTI - Roza, Melia (RC-INSTITUT, 2019)
This research was motivated by the understanding of the mathematical concepts of class VII students of SMPN 1 Linggo Sari Baganti which were still low and the learning process was still conventional, so students were less active in learning. One of the actions that can be taken is to apply the cooperative learning model Index Card Match (ICM) type. This study aims to determine whether understanding mathematical concepts of students using cooperative learning models Index Card Match (ICM) type is better than understanding students' mathematical concepts using conventional learning. This type of research is a quasi-experimental, the population in this study were all VII grade students of SMPN 1 Linggo Sari Baganti consisting of 5 classes. Sampling by Random Sampling, the sample in this study was class VII1 as the experimental class and class VII3 as the control class. The instrument in this study is a test of the ability to understand mathematical concepts. Analysis of the data used is the t test. Hypothesis test results obtained t_count = 1.912 and t_table = 1.672 with α = 0.05 and dk = 57, so t_count> t_tabel. This means rejecting Ho, which means that understanding mathematical concepts of students using cooperative Index Card Match (ICM) type is better than understanding students' mathematical concepts using conventional learning.